Analisis Pengaruh Utang Luar Negeri Dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Indonesia - Zaskya Humairah (Universitas Labuhanbatu, 2023)
This study was conducted to determine and analyze the effect of external debt and government spending on economic growth, in this case GDP. The sample used is time series data from the period 1985-2014 on foreign debt, government spending and GDP ( Gross Domestic Product) taken from World Bank data. The sample in this study berjumalh 30 data that will be used as the object of research. The dependent variable in this study is economic growth using data on Indonesia'S GDP, while the independent variable is the external debt and expenditure of the Government of Indonesia. To see the effect of independent variables and dependent variables, researchers perform multiple linear regression analysis test also perform classical assumption test. Based on the research results obtained, it can be seen that simultaneously foreign debt and government spending have a significant effect on Indonesia's economic growth. Furthermore, partially, foreign debt has a positive and significant effect on economic growth, and government spending also has a positive and significant effect on Indonesia's economic growth.